Multiparametric renal magnetic resonance imaging: validation, interventions, and alterations in chronic kidney disease - Cox, Eleanor F.; Buchanan, Charlotte E.; Bradley, Christopher R.; Prestwich, Benjamin; Mahmoud, Huda; Taal, Maarten; Selby, Nicholas M.; Francis, Susan T. (Frontiers Media, 2017)
Background: This paper outlines a multiparametric renal MRI acquisition and analysis protocol to allow non-invasive assessment of hemodynamics (renal artery blood flow and perfusion), oxygenation (BOLD T2*), and microstructure (diffusion, T1 mapping).